Financial performance analysis of Saudi Riyad bank (2020-2024) - Mahmoud, Mutaz T. (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the financial performance of Saudi banks, with a specific focus on Riyad Bank during the period 2020–2024. It uses a set of key financial ratios, the analysis examines liquidity ratios, solvency ratios, non-performing loans, profitability ratios, and utilization ratios. The paper aims to determine the stability of the bank's financial performance and provide recommendations for maintaining and improving the positives and addressing and mitigating weaknesses. The study employs an analytical approach to evaluate financial data collected from the annual reports of Riyad Bank and the Saudi Central Bank for the period from 2020 to 2024. The analysis aims to assess the financial performance of Saudi banks in general and to evaluate the performance of Riyad Bank in particular. The results show that the liquidity ratio analysis showed that the bank may need to re-evaluate its liquidity management strategies to ensure that it can meet its obligations, especially sudden or large withdrawal requests. The bank's solvency ratio increased overall, peaking in 2023 (107.9%); starting in 2024 (104.5%), the bank is making efforts to improve its solvency and increase its capital. The paper noted that the non-performing loan ratio was low during the study period. The return on equity showed that the bank has significantly improved its ability to generate earnings from its equity. The return on assets analysis indicates that the bank has demonstrated excellent asset management efficiency. The bank's efficiency ratio declined, indicating that the bank was able to control its expenses relative to revenue growth. The utilization ratio analysis shows a shift toward increased lending after 2020; the bank should ensure that it maintains strong liquidity management and risk controls to protect against the risks associated with lending more than its deposits. This paper contributes to the analysis and evaluation of the financial performance of Saudi banks, focusing on Riyad Bank, one of the largest leading banks listed on the Saudi Capital Market Authority. The aim is to maintain and develop positives and address deviations to mitigate financial, market, operational, and legal risks. It also provides administrative and operational insights into the bank's performance to enhance its reputation, market value, and competitive advantage. The findings are based on historical data and may not fully reflect the current or future performance of the bank. The results provide important administrative and operational insights for Riyad Bank to enhance its reputation, market value, and competitive advantage, thereby fulfilling its mission to society. The study emphasizes the importance of analysing the financial performance of Saudi banks to preserve positives and mitigate negatives, which aids in financial decision-making and contributes to the stability and efficiency of bank operations.